The Green Golden Rule: Habit and anticipation of future consumption - Jo\~ao Ricardo Faria; Peter McAdam (European Central Bank (ECB), 2019)
We derive the Green Golden Rule (GGR) in the Habit Formation (HF) and Anticipation of Future Consumption (AFC) frameworks. Since consumption is the key variable of GGR, time non-separabilities in preferences over consumption streams, given by the AFC and HF, may have important impacts on the environment and sustainability. We demonstrate that agents who smooth their consumption patterns, according to the HF hypothesis, are more likely to preserve the environment than those who anticipate future consumption or who do not so smooth consumption.
Keywords: D90; Q56; 330; Sustainability; Environment; Resources; Growth